Pengembangan Aplikasi Area untuk Meningkatkan Pemahaman Matematis Siswa pada Materi Keliling Bangun Datar Kelas V - Lestari, Wulan Sri; Irawati, Riana; Maulana, Maulana (AS-SABIQUN, 2025)
This investigation was prompted by pupils' inability to comprehend the diameter of two-dimensional figures. Students often experience boredom in studying due to the teacher's exclusive reliance on lecture methods, which adversely impacts their comprehension of the circumference of planar shapes. This research aims to create an Android-based application named AREA to enhance fifth-grade students' comprehension of flat figures at SD Negeri Setiajaya 01 and to evaluate its practicality. The employed research methodology is Research and Development (R&D) utilizing the ADDIE model for the development phase. The research instruments employed included validation sheets for material experts, media experts, pretest-posttest questionnaires, and response surveys for teachers and students. Data analysis methodologies for expert and educator validation are assessed via a Likert scale; thereafter, pretest and posttest evaluations employ N-Gain formula analysis, while media appropriateness is gauged by questionnaires directed at instructors and students. The research findings indicate that the Android-based AREA media is highly valid for usage, as evidenced by validation results from material and media specialists, which yielded an average percentage of 98% in the highly viable category. The media's suitability can be assessed through the teacher questionnaire results, which yielded a score of 92%, and the student response questionnaire, which indicated a score of 99%. According to these findings, AREA media can be classified as highly appropriate for educational purposes. Apart from that, the N-gain persent or N-gain percentage results were also abtained at 66,93% so that based on these result it can be said that AREA media is “effective enough” to be used in the learning process.